Representasi Realitas Sosial dan Humanisme dalam Cerpen Filosofi Kopi: Kajian Sosiologi Sastra - Rahmat Afdal; Abdurahman Abdurahman (Indo Publishing, 2026)
This study aims to analyze the short story Filosofi Kopi by Dee Lestari using a sociological literary approach drawn from the theoretical frameworks of Sapardi Djoko Damono, Alan Swingewood, and Lucien Goldmann. This short story is one of the richest contemporary Indonesian literary works in terms of social reality representation, encompassing coffee culture as a symbol of urban middle-class identity, friendship dynamics under economic pressure, tensions between traditional values and modernization, and the resistance of local wisdom against global capitalist domination. The research method employed is descriptive qualitative with close reading, note-taking, and analysis techniques. The theoretical foundations include: (1) Sapardi Djoko Damono's literary sociology theory regarding literary works as a mirror of social life; (2) Swingewood's approach to literature as a sociocultural document and ideological expression of social groups; and (3) Goldmann's genetic structuralism that examines the author's vision du monde in relation to social class. The findings indicate that Filosofi Kopi effectively represents the social reality of early twenty-first century urban Indonesian society, embodies a humanist world view transcending class boundaries, and fulfills social functions as a critique of consumer culture as well as an internalization of humanistic values. This study is expected to enrich the field of literary sociology applied to contemporary Indonesian literary works.